Sex Education with the Theme "Healthy, Smart and Cheerful" - Ni Nyoman Sri Artina Dewi; Agustina Ida Pratiwi; Dyah Woro Kartiko Kusumo Wardani; Dewi Novitasari Suhaid; Eviyani Margaretha Manungkalit; Lorensia Panselina Widowati; Yetty Leoni Irawan; Margaretha Kusmiyanti (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
Sex education is very important to give to teenagers, even from childhood. Children and adolescents are vulnerable to misinformation about sex. People's views in general are still taboo when talking about sex and sexuality issues. If sex education is not taught as early as possible to children, it is likely that there will be violations of moral values such as free sex, rape, etc. Some efforts that can be made to overcome reproductive health problems in adolescents include sexual education. Sexual education is an effort to increase knowledge and change individual attitudes and behaviors to better understand their reproductive health needs. The purpose of this community service is to increase students' knowledge related to sex education. At the beginning of this activity, it began with an approach with partners, namely to see how many students and female students participated, for effectiveness in counseling. The participants who participated in this counseling were fourth grade students at Ricci Elementary School, Jalan Kemenangan III N0 47 Glodok, Taman Sari, West Jakarta, consisting of 48 male students and 33 female students. The total number of participants who participated in this counseling was 81. This counseling activity was declared successful because there was an increase in knowledge in students and schoolgirls after being given counseling.